Some estimates for a special linear difference parabolic equation - Štikonas, Artūras (Mathematical Modelling and Analysis, 1997)
The finite‐difference scheme for a special linear parabolic equation is investigated. A priori estimates for such finite‐difference scheme are derived in the difference analogues of norm on Banach function spaces V2 and W 2 2,1.First Published Online: 14 Oct 2010